2014
DOI: 10.5812/jjm.10135
|View full text |Cite
|
Sign up to set email alerts
|

Infected Hydatid Cysts Bacteria in Slaughtered Livestock and Their Effects on Protoscoleces Degeneration

Abstract: Background:The protoscoleces of fertile hydatid cysts are considered as major risks in surgery and producing secondary cysts if rupture the cyst during operation and, cause infecting the dogs with adult worm if eaten by this animal. Bacterial infection of the hydatid fluid can lead to sterilization of the cyst.Objectives:The aim of this study was to determine the bacterial infection rate of livestock hydatid cysts in Hamedan, Iran, and test the isolated bacteria effects on viable protoscoleces, in vitro.Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
(23 reference statements)
5
9
0
Order By: Relevance
“…Interestingly, the most of cyst recovered from inspected cattle were multilocular form and nearly 80% of them were found suppurative or calcified. This result was confirmed with previous study which is conducted in the region that reported 88% suppuration or calcification rate of cattle cysts (14).…”
supporting
confidence: 83%
“…Interestingly, the most of cyst recovered from inspected cattle were multilocular form and nearly 80% of them were found suppurative or calcified. This result was confirmed with previous study which is conducted in the region that reported 88% suppuration or calcification rate of cattle cysts (14).…”
supporting
confidence: 83%
“…Hence, understanding the fertility and viability of the hydatid cysts in the intermediate host is critical because livestock play as the main source of infection transmission of the final host by consuming fertile cysts. The fertility of the hydatid cyst is different in various geographical situations, animal species, locations, size, and genotype of the cyst [48]. There are many reports about the infertility rate of the hydatid cysts in various genotypes and animal species in different regions [36,49], indicating that fertility depends on the genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the most common bacterial isolates were P. aeruginosa, K. oxytoca, E. amnigenus, and E. aerogenes, indicating that gram negative bacteria are the most common bacterial invaders in hydatid cysts. Gram-negative bacteria were identi ed from 87.1 percent of hepatic and 85.4 percent of lung hydatid cyst uid in sheep, with E. coli and K. pneumoniae being the most common isolates, according to similar studies (Abdullah et al 2021;Fallah et al 2014;Khleifat et al 2010). In contrast, S. aureus was recovered from hepatic hydatid cyst uids in a recent test, demonstrating that the types of bacteria isolated from the cyst uids are highly varied et al 2020 ).This could be due to the infective stages ability to live in the outside environment, as well as the life cycle of Echinococcus spp., which entails tissue translocation into the intermediate host.…”
Section: Discussionmentioning
confidence: 93%
“…According to one theory, intermediate animals such as sheep and goats swallow bacteria-infected Echinococcus spp. eggs(Ahmed et al 2021;Fallah et al 2014). When these eggs reach the colon, they hatch, and the bacterially tainted oncosphere embryo penetrates the mucosa, eventually forming hydatid cysts in the liver and lungs.…”
mentioning
confidence: 99%